Meta-analysis of tumor necrosis factor alpha -308 polymorphism and knee osteoarthritis risk - Kou, Suotang (BMC Musculoskelet Disord, 2014)
BACKGROUND: Several case–control studies have been conducted to clarify the association between the tumor necrosis factor alpha (TNF-α) -G308A polymorphism and risk of osteoarthritis (OA); however, the results are inconsistent. This meta-analysis was performed to clarify this issue using all the available evidence. METHODS: Eligible articles were retrieved by searching PubMed, Web of science and Google scholar. The strength of the association between the TNF-α -G308A polymorphism and risk of OA was assessed by odds ratios (ORs) with the corresponding 95% confidence interval (CI) for each study. RESULTS: Seven studies were included in the meta-analysis, which included 983 OA cases and 1355 controls. The pooled analysis based on all included studies showed a significantly increased OA risk in the recessive genetic model analysis (OR = 11.08, 95% CI = 4.75-25.86, p < 0.001) and in the A allele vs. G allele analysis (OR = 2.30, 95% CI = 1.08-4.90). However, there was no statistical difference in the dominant genetic model analysis (OR = 2.45, 95% CI = 0.95-6.27, p = 0.06). Furthermore, we found that OA patients had a higher frequency of the AA genotype (OR = 10.49, 95% CI = 4.47-24.61) and GA genotype (OR = 1.78, 95% CI = 1.03-3.08) compared with the control population. CONCLUSION: Our results suggested that the TNF-α -G308A polymorphism were associated with an increased risk of OA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2474-15-373) contains supplementary material, which is available to authorized users.